Quadratic subfields on quartic extensions of local fields - Joe Repka (International Journal of Mathematics and Mathematical Sciences)
We show that any quartic extension of a local field of odd residue characteristic must contain an intermediate field. A consequence of this is that local fields of odd residue characteristic do not have extensions with Galois group A4 or S4. Counterexamples are given for even residue characteristic.